2001
DOI: 10.1046/j.1365-2117.2001.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analogue flume‐model study of river–shelf systems: principles and verification exemplified by the Late Quaternary Colorado river–delta evolution

Abstract: Physical modelling of clastic sedimentary systems over geological time spans has to resort to analogue modelling since full scaling cannot be achieved within the spatial and temporal restrictions that are imposed by a laboratory set‐up. Such analogue models are suitable for systematic investigation of a sedimentary system's sensitivity to allocyclic changes by isolating governing parameters. Until now, analogue models of landscape evolution were mainly qualitative in nature. In this paper, we present a quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…In fact, correlations between onshore and offshore records, such as that presented above for the Texas coastal plain and shelf records, demonstrate that long-held concepts of incision and complete sediment bypass during falling sea-level are not realistic, and that incision updip is not necessary to produce the volume of sediments required to produce systems tracts farther downdip. Van Heijst et al (2001) drew similar conclusions through experimental flume studies, and comparisons with the OIS 3 record of the Colorado River offshore.…”
Section: Falling Stage To Lowstand Systems Tractsmentioning
confidence: 54%
“…In fact, correlations between onshore and offshore records, such as that presented above for the Texas coastal plain and shelf records, demonstrate that long-held concepts of incision and complete sediment bypass during falling sea-level are not realistic, and that incision updip is not necessary to produce the volume of sediments required to produce systems tracts farther downdip. Van Heijst et al (2001) drew similar conclusions through experimental flume studies, and comparisons with the OIS 3 record of the Colorado River offshore.…”
Section: Falling Stage To Lowstand Systems Tractsmentioning
confidence: 54%
“…The question of the statistics of channel network establishment was explored in a pioneering paper by Howard et al [6], in which the authors showed that braided channel paths exhibit scaling relationships similar to those derived from random walk models. At a larger scale, diffusion has been invoked as a useful tool to model landscape evolution in a variety of field and laboratory settings, including braided river equilibrium profiles [20,21,[25][26][27][28]. These macroscopic applications of diffusion to braided river evolution have not, however, been linked to underlying stochastic dynamics as in classical Brownian motion [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of numerical and physical stratigraphic modelling experiments are not straightforward to compare with outcrop and subsurface geological data, and have only sparingly been used as a basis to interpret observations made on such data (e.g. Muto & Steel 1992, 2002Van Heist et al 2001;Paola & Martin 2012). In this paper, I re-examine the stratal architectures exposed in continuous, large-scale outcrops of marginal-marine and shallow-marine strata (late Cretaceous Star Point Sandstone, Blackhawk Formation, lower Castlegate Sandstone and related strata exposed in the Wasatch Plateau and Book Cliffs, Utah and Colorado, USA), from which widely applied conceptual models of high-resolution sequence stratigraphy that invoke a relative sea-level control were developed during the 1980s and 1990s (e.g.…”
mentioning
confidence: 99%